2023
DOI: 10.1128/aac.01550-22
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Ganciclovir in Allogeneic Hematopoietic Stem Cell Transplant Patients

Abstract: Treatment of cytomegalovirus (CMV) infection in allogeneic hematopoietic stem cell transplantation (alloHCT) patients with ganciclovir is complicated by toxicity and resistance. This study aimed to develop an intravenous ganciclovir population pharmacokinetic model for post-alloHCT patients and to determine dosing regimens likely to achieve suggested therapeutic exposure targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Numerous pharmacokinetic studies have been conducted in transplantation in adult and pediatric populations [19,41 ▪ ,42,43]. The most common structural population pharmacokinetic (PK) model utilized was a two-compartment model with lagged first-order absorption (for oral ValGCV) and elimination from central compartment [19,34,42,44–46].…”
Section: Population Pharmacokinetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous pharmacokinetic studies have been conducted in transplantation in adult and pediatric populations [19,41 ▪ ,42,43]. The most common structural population pharmacokinetic (PK) model utilized was a two-compartment model with lagged first-order absorption (for oral ValGCV) and elimination from central compartment [19,34,42,44–46].…”
Section: Population Pharmacokinetic Modelsmentioning
confidence: 99%
“…One study identified the type of SOT as a significant covariate for GCV clearance with kidney transplant recipients having higher clearance compared to lung, liver, or heart transplant recipients [44]. In comparison, covariates identified in hematopoietic stem cell transplant (HCT) recipients included creatinine clearance as estimated by Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) and the presence of continuous renal replacement therapy [41 ▪ ]. Studies comparing ValGCV in HCT recipients with and without Grade I–II gastrointestinal graft-versus-host-disease (GVHD) did not find a significant difference in exposures achieved [23,47].…”
Section: Population Pharmacokinetic Modelsmentioning
confidence: 99%